Primary pleural leiomyosarcoma presenting as multiple pleural masses - Ozyurtkan, Mehmet Oguzhan; Akin, Mustafa (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2015)
In this article, we report a 74-year-old female patient with primary pleural leiomyosarcoma presenting with three pleural masses. Two diaphragmatic masses were completely excised via thoracoscopy. A positron emission tomography showed the apical mass as the primary site of origin, which was completely excised via axillary thoracotomy. As surgical margins were negative, patient was not given chemo- or radiotherapy, and is disease-free after 17 months of follow-up. Surgical resection is the mainstay of treatment of leiomyosarcoma. In nonmetastatic cases or when the surgical margins are negative, postoperative chemo- or radiotherapy may not be required. To our knowledge, there is no case of primary pleural leiomyosarcoma presenting with multiple pleural masses reported in the literature.
Keywords: Leiomyosarcoma; pleura; thoracotomy; video-assisted thoracic surgery